Evaluating the suitability of the Immediate Post-Concussion Assessment and Cognitive Testing (ImPACT) computerized neurocognitive battery for short-term, serial assessment of neurocognitive functioning. (April 2019) - Elbin, R.J.; Fazio-Sumrok, Vanessa; Anderson, Melissa N.; D'Amico, Nathan R.; Said, Azkya; Grossel, Adam; Schatz, Philip; Lipinski, Damon; Womble, Melissa
Highlights: ImPACT can be used serially over a one-hour period. Neurocognitive scores did not differ across administrations. A small percentage of scores were outside RCI cutoffs, suggesting sufficient one-hour reliability. Abstract: Background: Computerized Neurocognitive Testing (CNT) is frequently used for serial assessment of athletes following concussion. The Immediate Post-Concussion Assessment for Cognitive Testing (ImPACT) is a commonly used CNT with well-documented test–retest reliability in healthy samples for intervals ranging from one month to two years. However, previous research has not explored use of ImPACT for other serial testing methodologies such as immediately before and after an experimental trial/intervention where administration on the same day may be necessary. Purpose: To examine the suitability of ImPACT for short-term, serial assessment of neurocognitive functioning. Study design: Prospective, repeated measures research design. Methods: Forty-two healthy, college-aged individuals completed ImPACT twice, with a one-hour break between assessments. Reliability was assessed using Pearson correlation coefficients, intraclass correlation coefficients (ICCs), reliable change indices (RCIs) and regression-based methods (RBM). Results: No significant increases in mean ImPACT composite or symptom scores were observed between assessments. ICCs ranged from 0.34 to 0.74 (single)/0.51 to 0.85 (average). Across two test administrations, 92–100% and 93–98% of participants' change scores fell within cutoffs when utilizing the RCI and RBM, respectively. Conclusion: The ICCs for ImPACT composite and factor scores across the one-hour administration were consistent with previous studies. Only a small percentage of scores fell outside of RCI and RBM cutoffs. These statistical metrics suggest that ImPACT has sufficient reliability when repeating administration within one-hour.